A Facile synthesis of silver modified ZnO nanoplates for efficient removal of ofloxacin drug in aqueous phase under solar irradiation. Issue 3 (June 2018) - Kaur, Amandeep; Gupta, G.; Ibhadon, Alex O.; Salunke, Deepak B.; Sinha, A.S.K.; Kansal, Sushil Kumar
Highlights: Silver modified ZnO photocatalysts were synthesized by hydrothermal method. Silver modified ZnO plates exhibited improved photodegradation performances. The improved photoactivity is attributed to the separation of charge carriers. Abstract: Here we report, silver modified ZnO was successfully synthesized via hydrothermal method. The as-prepared material was further characterized in detail for their structural, morphological and optical properties using X-ray diffraction, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, transmission electron microscopy, UV- diffuse reflectance spectroscopy and photoluminescence spectroscopy. X-ray photoelectron spectroscope analysis confirmed the existence of metallic silver in the prepared catalyst. The band gap for silver modified ZnO has been estimated from Tauc's plot and found to be 3.10 eV. Further, the synthesized catalyst was used as efficient photocatalyst for the degradation of antibiotic drug, i.e. ofloxacin, under solar irradiation. The detailed photocatalytic experiments revealed that silver modified ZnO (0.25 g/L) exhibited ∼98% photocatalytic degradation of ofloxacin (10 mg/L, pH 7) in 150 min under solar illumination. The prepared silver modified ZnO exhibited higher photocatalytic activity compared to the bare ZnO. This enhancement in phtocatalytic activity could be firstly due to efficient charge separation and secondly due to silver nanoparticles acting as electron sink on ZnO surface. The photocatalytic degradation of ofloxacin fitted well with pseudo first order kinetic model. Moreover, the intermediates were proposed using LCMS technique and possible degradation pathway was developed.